Euthanasia in the practice of the European Court of Human Rights - Kovačević Dušica G. (Anali Pravnog Fakulteta u Beogradu, 2023)
The paper aims to shed light on the interpretation of mercy killing, i.e., euthanasia, in European Court of Human Rights cases. This controversial phenomenon has a specific legal status. More specifically, due to the complexity of euthanasia, it is impossible to create universally accepted international standards. On the other hand, modern society creates a need to expand the legal boundaries regarding bioethical issues related to the compassionate end-of-life care. The European Court of Human Rights is a unique international organization that interprets universal legal documents, especially the European Convention on Human Rights, in the context of euthanasia. Bearing this in mind, it is important to collect and analyze the information resulting from the specific decision-making process of the European Court of Human Rights. The Court's past and future similar cases will certainly affect the future legal status of euthanasia both internationally and at the level of member states.